2014
DOI: 10.3109/01902148.2014.977461
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar NF-κB signaling regulates endotoxin-induced lung inflammation

Abstract: Overexpression of NF-κB targeted to the lung epithelium worsened lung inflammation and injury in response to LPS exposure while conditional deletion of NF-κB signaling reduced lung inflammation. Lung inflammation and injury were associated with increased cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Clinical research has reported that the degree of NF-jB activation was increased in patients with sepsis or acute lung injury (Schwartz et al 1996). Additionally, animal studies showed that inactivation of NF-jB pathway by pharmacological inhibition or gene modification decreased the expression of pro-inflammatory mediators and diminished the severity of endotoxemia-induced acute lung injury Lopez et al 2015). In the present study, the nuclear proteins from lung tissues were extracted.…”
Section: Discussionmentioning
confidence: 83%
“…Clinical research has reported that the degree of NF-jB activation was increased in patients with sepsis or acute lung injury (Schwartz et al 1996). Additionally, animal studies showed that inactivation of NF-jB pathway by pharmacological inhibition or gene modification decreased the expression of pro-inflammatory mediators and diminished the severity of endotoxemia-induced acute lung injury Lopez et al 2015). In the present study, the nuclear proteins from lung tissues were extracted.…”
Section: Discussionmentioning
confidence: 83%
“…AECII can decrease surface tension to prevent atelectasis and absorb fluid to prevent pulmonary edema. AECII help maintain normal air exchange function of the lung, and possess stem cell function in lung development and damage repair [5,6]. Because the biological characters of AECII are highly dependent on lung microenvironment, AECII would lose specific characteristics and differentiate into AECI after in vitro culture [22].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal inflammatory response to cigarette smoke in the lung promotes COPD development [4]. Alveolar type II epithelial cells (AECII) play important role in the maintenance of normal lung structure and help the repair and recovery of the lung after biological and physical lung damages [5,6]. Cigarette smoking has been shown to cause the apoptosis of AECII [7].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate re-epithelialization following injury triggers a cascade of events leading to pathological fibrosis. Increased type II alveolar epithelial cell (AECII) apoptosis and senescence are considered to have important roles in the development of pathological fibrosis in IPF and ARDS (Matute-Bello et al, 1999 ; Plataki et al, 2005 ; Hecker et al, 2014 ; Lopez et al, 2015 ). Following injury, the stages of fibrosis in cardiac and respiratory disease are similar, as are the cellular and molecular mechanisms that lead to scar formation.…”
Section: Molecular and Cellular Fibrotic Mechanismsmentioning
confidence: 99%